PENERAPAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 KE DALAM PUTUSAN HAKIM - , Raharjo Ari Nugroho, Ageng Marta Kusuma (Fakultas Hukum Universitas Sebelas Maret, 2014)
Abstract This research aims to find out the application of Article 9 of Act Number 23 of 2004 about the Domestic Violence Removal into the Judge of Religion Courtâs verdict so that the judgeâs verdict can fulfill the feeling of justice for the victim due to the domestic negligence action and to find out the factor causing the domestic violence, the form of which is negligence in household. This study belongs to a normative law research that is descriptive in nature. The data of research included primary and secondary data. The primary data was the main data of research. Meanwhile the secondary data was used to support the primary data. Techniques of collecting data used were library study and interview methods. The data obtained was then analyzed using an analytical descriptive method. The result of research showed that majority judges of Religion Court have not had sensitivity in deliberating their verdict by including the Domestic Violence Removal Act into legal deliberation in adjudicating the divorce case. In practice, the judges of Religion Court still rarely integrate such the act that is expected to minimize the domestic violent action. The benefit obtained from this research was that it gave a description about the problem studied and could be used as the input material to those experiencing and involved directly in this problem. Keywords : Application, Domestic Violence, Judgeâs Verdict